Comparison of the calculation results of heat exchange between a single-family building and the ground obtained with the quasi-stationary and 3-d transient models. Part 1: continuous heating mode = Porównanie wyników obliczeń wymiany ciepła jednorodzinnego budynku mieszkalnego z gruntem uzyskanych za pomocą metody quasi-stacjonarnej oraz modelu niestacjonarnego trójwymiarowego. Część I: ogrzewanie ciągłe - Staszczuk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper provides comparative results of calculations of heat exchange between ground and typical residential buildings using simplified (quasi-stationary) and more accurate (transient, three-dimensional) methods. Such characteristics as building?s geometry, basement hollow and construction of ground touching assemblies were considered including continous heating mode.
Keywords: wymiana ciepła; wymiana ciepła z gruntem; ogrzewanie ciągłe; obliczenia quasi-stacjonarne; budynek jednorodzinny; heat transfer via the ground; heat exchanger; continuous heating; quasi-stationary calculations; single-family building